(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The Jaddala Formation in Bai Hassan and Kirkuk oil fields was deposited on a carbonate platform with an open shelf setting. Microfacies analysis revealed that deposition took place within three zones; they include the Toe of slope, Deep shelf, and Deep basin. The succession consists of four third order cycles representing successive intervals of relative sea level rises and stillstand. The nature of cycle symmetry and thicknesses suggest that the tectonic component is the main controlling factor on cycle development in highly subsiding basin.